2013
DOI: 10.2196/jmir.2653
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Genetics and Smoking Through Social Media: Are We There Yet?

Abstract: BackgroundSocial media is a recent source of health information that could disseminate new scientific research, such as the genetics of smoking.ObjectiveThe objectives were (1) to evaluate the availability of genetic information about smoking on different social media platforms (ie, YouTube, Facebook, and Twitter) and (2) to assess the type and the content of the information displayed on the social media as well as the profile of people publishing this information.MethodsWe screened posts on YouTube, Facebook,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…[9][10][11][12][13][14][15] Some study results also concluded that health education through social media about the dangers of smoking led to reduced cigarette consumption in adolescents. [16][17][18][19][20] The results of this study are not in line with study on the effectiveness of health promotion with leaflets and video media on adolescent knowledge indicating that adolescent knowledge is sufficient and promotes good attitudes after receiving counseling alone about smoking behavior. 10 A study conducted at the Surakarta Vocational School, 3 on the effects of health education on cigarette smoking in adolescents revealed that to increase adolescent knowledge and attitudes about the dangers of smoking, health education is expected to stop smoking habits and avoid smoking to begin with.…”
Section: Discussioncontrasting
confidence: 59%
“…[9][10][11][12][13][14][15] Some study results also concluded that health education through social media about the dangers of smoking led to reduced cigarette consumption in adolescents. [16][17][18][19][20] The results of this study are not in line with study on the effectiveness of health promotion with leaflets and video media on adolescent knowledge indicating that adolescent knowledge is sufficient and promotes good attitudes after receiving counseling alone about smoking behavior. 10 A study conducted at the Surakarta Vocational School, 3 on the effects of health education on cigarette smoking in adolescents revealed that to increase adolescent knowledge and attitudes about the dangers of smoking, health education is expected to stop smoking habits and avoid smoking to begin with.…”
Section: Discussioncontrasting
confidence: 59%
“…This result highlights the need to investigate the underlying mechanisms further and develop messages regarding the importance of FHH for individuals with limited health literacy. As genomic information plays an increasingly important role in medicine and public health, health literacy research is critically necessary in order to avoid increasing existing health inequalities in information, services, and health outcomes (De Viron, Suggs, Brand, & Van Oyen, 2013; Hurle et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Lower age and more education predicted higher eHealth literacy, and more education and being a female was associated with a high usage of Web 2.0 for retrieving health information [30][31][32]. Women [32] and teenagers [33] with a chronic disease were more active in engaging and participating in health-enhancing behaviors online than the general population.…”
Section: Influence Behaviormentioning
confidence: 97%
“…Women [32] and teenagers [33] with a chronic disease were more active in engaging and participating in health-enhancing behaviors online than the general population. Young people extensively used Facebook privacy settings and intentionally disclosed only a few pieces of personal health information to all of their Facebook friends [34].…”
Section: Influence Behaviormentioning
confidence: 97%